Integrated structural study of the FrpD protein from Neisseria meningitidis - Sviridova, Ekaterina (Jihočeská univerzita, 2016)
Neisseria meningitidis (N. meningitidis) is a Gram-negative commensal bacterium colonizing nasopharynx of about 10 % of healthy individuals, which can cause invasive diseases, such sepsis and meningitis, upon occasional penetration into bloodstream. Pathogenesis of N. meningitidis appears to be directly related to conditions of limited iron availability. Under these conditions two proteins of unknown function: FrpC and FrpD, are synthesized. FrpD is a highly conserved lipoprotein of N. meningitidis anchored to the bacterial outer membrane. It is known that FrpD tightly binds the FrpC protein, which belongs to the Repeat-in-Toxin (RTX) protein family and may act as bacterial exotoxin. However, the mechanism of FrpD-FrpC interaction and the exact function of this complex are unknown due to the absence of structural information on these proteins. Therefore, we set out to determine the structure of FrpD and provide insights into its interaction mechanism with FrpC and structure-functional relationships of these two proteins. We determined the first crystal and solution structures of the FrpD protein. We found that atomic structures of FrpD reveal a novel protein fold. We uncovered the structure-function relationships underlying the mechanism of interaction between the FrpD and FrpC proteins and tested the putative function of the FrpD-FrpC1-414 complex in vitro. Finally, we proposed the putative function of the FrpD-FrpC1-414 complex as a new minor adhesin of N. meningitidis, which mediates the bacterial adhesion to the host epithelial cells and facilitate the colonization. Our work constitutes the first step in clarifying the molecular basis of the FrpD-FrpC interaction and sets the base for further investigation of the role of FrpD and FrpC in the virulence mechanism of N. meningitidis.
Integrated structural study of the FrpD protein from Neisseria meningitidis
Keywords: Iron-regulated protein; Neisseria meningitidis; FrpD; FrpC; unknown function; novel fold; adhesins; X-ray crystallography; Iron-regulated protein; Neisseria meningitidis; FrpD; FrpC; unknown function; novel fold; adhesins; X-ray crystallography